2024
DOI: 10.1152/physrev.00006.2023
|View full text |Cite
|
Sign up to set email alerts
|

Lung endothelium, tau, and amyloids in health and disease

Abstract: Lung endothelium in the arteries, capillaries, and veins are heterogeneous in structure and function. Lung capillaries in particular represent a unique vascular niche, with a thin yet highly restrictive alveolar-capillary barrier that optimizes gas exchange. Capillary endothelium surveys the blood while simultaneously interpreting cues initiated within the alveolus and communicated via immediately adjacent type I and type II epithelial cells, fibroblasts, and pericytes. This cell-cell communication is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 585 publications
0
7
0
Order By: Relevance
“…Second, while our data suggest the transcriptomic changes in microglia we observe in patients with COVID-19 are induced by TNF-α and other cytokines, we cannot infer causality from these observational data. As an alternative hypothesis, tissue hypoxia resulting from COVID-19-induced vascular injury could account for inflammatory activation of microglia through HIF-1α (31,(70)(71)(72)(73), or cognitive dysfunction may result from other lung-derived damage-associated molecular patterns, neurotoxic agents, or pro-inflammatory molecules (74)(75)(76). Third, the administration of corticosteroids in our observational cohort was not randomized and did not include a placebo control.…”
Section: Discussionmentioning
confidence: 99%
“…Second, while our data suggest the transcriptomic changes in microglia we observe in patients with COVID-19 are induced by TNF-α and other cytokines, we cannot infer causality from these observational data. As an alternative hypothesis, tissue hypoxia resulting from COVID-19-induced vascular injury could account for inflammatory activation of microglia through HIF-1α (31,(70)(71)(72)(73), or cognitive dysfunction may result from other lung-derived damage-associated molecular patterns, neurotoxic agents, or pro-inflammatory molecules (74)(75)(76). Third, the administration of corticosteroids in our observational cohort was not randomized and did not include a placebo control.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently identified a novel host response to pneumonia that may contribute to end-organ dysfunction and offers a novel therapeutic target. Pneumonia elicits production of cytotoxic tau and amyloids within the lung; these cytotoxins are heat and protease stable, are transmissible between cells and animals, consistent with prion disease, and are sufficient to injure naïve organs, including the lung, heart, and brain [13][14][15][16][17]. While these prior studies demonstrated that pneumonia initiates a proteinopathy of the lung, this principle has not been tested in a controlled patient cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, HBSS washes from extra-corporeal membrane oxygenation oxygenators of infected patients, but not uninfected patients, contain tau and amyloids that are toxic to naïve animals [16]. While these results illustrate the contribution of infection-elicited cytotoxic tau and amyloids to end-organ dysfunction in pre-clinical animal models [15], the infectious proteinopathy hypothesis has not been tested in a prospective clinical study.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations